Sex work and HIV in Cambodia: trajectories of risk and disease in two cohorts of high-risk young women in Phnom Penh, Cambodia - Page, Kimberly (BMJ Publishing Group, 2013)
OBJECTIVES: HIV prevalence among Cambodian female sex workers (FSW) is among the highest in Southeast Asia. We describe HIV prevalence and associated risk exposures in FSW sampled serially in Phnom Penh, Cambodia (Young Women's Health Study (YWHS)), before and after the implementation of a new law designed to combat human trafficking and sexual exploitation. DESIGN: Cross-sectional analysis of baseline data from two prospective cohorts. SETTING: Community-based study in Phnom Penh, Cambodia. PARTICIPANTS: Women aged 15–29 years, reporting ≥2 sexual partners in the last month and/or engaged in transactional sex in the last 3 months, were enrolled in the studies in 2007 (N=161; YWHS-1), and 2009 (N=220; YWHS-2) following information sessions where 285 and 345 women attended. PRIMARY OUTCOMES: HIV prevalence, sexual risk behaviour, amphetamine-type stimulant (ATS) and alcohol use, and work-related factors were compared in the two groups, enrolled before and after implementation of the new law. RESULTS: Participants in the two cohorts were similar in age (median 25 years), but YWHS-2 women reported fewer sex partners, more alcohol use and less ATS use. A higher proportion of YWHS-2 compared with YWHS-1 women worked in entertainment-based venues (68% vs 31%, respectively). HIV prevalence was significantly lower in the more recently sampled women: 9.2% (95% CI 4.5% to 13.8%) vs 23% (95% CI 16.5% to 29.7%). CONCLUSIONS: Sex work context and risk have shifted among young FSW in Phnom Penh, following implementation of anti-prostitution and anti-trafficking laws. While both cohorts were recruited using the same eligibility criteria, more recently sampled women had lower prevalence of sexual risk and HIV infection. Women engaging more directly in transactional sex have become harder to sample and access. Future prevention research and programmes need to consider how new policies and demographic changes in FSW impact HIV transmission.